Maple 13 Assisted Problem Based Teaching in Vector Calculus Course - T. Tutut Widiastuti A; Rahayu Kariadinata (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
The purpose of this study was to obtain learning outcomes by looking at the differences between classes learning of maple 13 application assisted by problem based teaching materials with convensional learning question and answer. The method used in this research is an experimental method with random sampling. The result of thi research are: (a) validation was carried out by competent expert lecturers to assess the feasibility of calculus vector questions to obtain good and very good criteria, so the valid test items were used for research, (b) from the validation results of the test items, 5 questions were used. The research (experiment) of 8 questions was tested, (c) the normality test was carried out on the N-gain and the postest score of class A (experiment), namely the class using Maple 13 application learning assisted by problem-based teaching materials and class B (control class ) by using learning with lectures and questions and answers, obtained a class A posttest score with a sig. 0.03 <0.05 means that class A (experimental) comes from a population that is not normally distributed, then the next test is the average difference test using the Mann Whitney test, (d) the average difference test between class A (experimental), namely the class using learning Maple 13 application assisted with problem-based teaching materials and class B (control class) using learning with lectures and questions and answers obtained from the Mann Whitney test with Asymp. Sig. (2-tailed) = 0.475> 0.05 means that between class A and class B have different averages but have the same level of achievement or there is no difference for the level of achievement of the average increase. Keywords: The Maple 13 Application Assisted By Problem-Based Teaching Materials, Calculus Vector